Auditor Adaptability in the Digital Age: A Qualitative Literature Review on the Interplay of Expertise, IT Literacy, and Dynamic Capabilities - Seger Santoso; Farah Qalbia; Ahembang (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review examines auditor adaptability in the digital age by synthesizing prior research on the interplay between professional expertise, IT literacy, and dynamic capabilities. Drawing on multidisciplinary studies in auditing, accounting information systems, and organizational theory, the review explores how digital technologies—such as data analytics, artificial intelligence, and automated audit tools—reshape auditors’ roles and competence requirements. The findings indicate that traditional audit expertise remains essential but is increasingly complemented by IT literacy, which enables auditors to effectively interpret technology-enabled evidence and reduce uncertainty in digital audit environments. Moreover, the dynamic capabilities framework explains how auditors continuously sense technological change, seize learning opportunities, and reconfigure audit practices to sustain audit quality. This review contributes to the auditing literature by conceptualizing auditor adaptability as a multidimensional and evolving capability, offering insights for audit firms, professional bodies, and educators in designing future-oriented competency development strategies.